Excitatory GABA induces BDNF transcription via CRTC1 and phosphorylated CREB‐related pathways in immature cortical cells. (18th July 2014) - Fukuchi, Mamoru; Kirikoshi, Yuya; Mori, Atsumi; Eda, Reika; Ihara, Daisuke; Takasaki, Ichiro; Tabuchi, Akiko; Tsuda, Masaaki
Abstract Although the excitatory action of GABA has been shown to activate the expression of brain‐derived neurotrophic factor (BDNF), its molecular mechanisms remain unclear. Using cultured rat cortical cells, we here demonstrated that GABA induced Bdnf mRNA expression mainly via L‐type voltage‐dependent Ca2+ channels (L‐VDCC) at the early stage and inhibited it at the late stage of the culture, which corresponded to the excitatory and inhibitory states of cortical cells. The excitatory GABA‐induced Bdnf mRNA expression was controlled by multiple Ca2+ signaling pathways including Ca2+/calmodulin‐dependent protein kinase (CaMK), mitogen‐activated protein kinase (MAPK) and calcineurin (CN). The Bdnf‐promoter IV (Bdnf‐pIV) was activated by GABA, mainly via cAMP‐response element (CRE)/CREB, and this was prevented by the over‐expression of a dominant negative CREB. The nuclear translocation of CREB‐regulated transcriptional coactivator 1 (CRTC1) was selectively induced by the GABA‐induced CN pathway to activate Bdnf‐pIV. On the other hand, GABA‐induced Gal4‐CREB‐dependent transcription, which was controlled by multiple Ca2+ signaling pathways, was prevented when the serine at position 133 of Gal4‐CREB was mutated to alanine. Taken together, the excitatory action of GABA transcriptionally activated Bdnf expression through the combination of nuclear‐localized CRTC1 and phosphorylated CREB in immature cortical cells, and may be the molecular mechanisms underlying Bdnf expression to control neuronal development. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> We demonstrated that GABA induced Bdnf expression at the early stage of the culture, in which GABA exerted its excitatory action. The excitatory GABA‐induced Bdnf expression was controlled by multiple Ca2+ signaling pathways evoked via L‐VDCC. Both the CREB coactivator, CRTC1 and CREB phosphorylation participated in excitatory GABA‐induced Bdnf transcription. Our present study indicates the mechanism underlying the excitatory GABA‐induced Bdnf expression in immature neurons and provide new insights into molecular mechanisms underlying Bdnf expression to control neuronal development.